Effect of Derivatives of Glycyrrhetic Acid on The Intensity of Free Radical Processes During Immobilization Stress (Texas Journal of Medical Science, 2022)
The effect of glycyrrhizic acid derivatives (18-dehydroglyceric acid - 18 DGA, monoammonium salt of glycyrrhizic acid - MSGA) on the intensity of free radical processes during immobilization stress was studied. The experiments were performed on mature male rats with an initial weight of 165–185 g. Experimental groups of animals were formed taking into account body weight. The animals were divided into 4 groups of 6 each. The first group consisted of healthy animals, while the rats of the remaining groups were subjected to immobilization stress. In contrast, in animals treated with a monoammonium salt of glycerol acid, the number of rats with mucosal injury was reduced by 2 times, and the number of linear and fine-dot wounds by 15.3 and 57.7%, respectively. The number of wounded rats was 67% and the Pauls index decreased to 64.1%. We noted high gastro protective activity in a group of animals treated with 18- dehydroglyceric acid. Thus, the number of mucosal injuries in this group of animals decreased by 65.3%, and the number of spot injuries decreased by 71.8%. It is noteworthy that the number of linear erosions decreased by 36.6%. From the data in Table 2 in these groups, it can be seen that the number of rats with ulcers decreased by 45%.